If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 45 = -65 Reorder the terms: 45 + 25x = -65 Solving 45 + 25x = -65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + 25x = -65 + -45 Combine like terms: 45 + -45 = 0 0 + 25x = -65 + -45 25x = -65 + -45 Combine like terms: -65 + -45 = -110 25x = -110 Divide each side by '25'. x = -4.4 Simplifying x = -4.4
| x+2=x*3 | | 10-23x=17 | | 7t-7=35 | | -2x-4(x+1)=5x+9 | | -2(3x+4)-x+6=-5x-2 | | 2(x+3)=(x-3) | | 23x-10=17 | | 8=4-2x | | 153.92/4 | | 2+p=9 | | 32-3x=12+7x | | 22+11=4x-7 | | 2x+33=63 | | 9.25x+1=10x+1 | | 0=x(2x-3)(4x+1) | | 5x+4=13+2x | | x/9-8=-5 | | 0.3x^2-48x+24=0 | | 58x=870 | | 9.25x=10x | | 2(3x+4)+8=-5x-4+9 | | 2-q/36 | | -51t=65t | | -51=65t | | 3x-4=3x-8 | | 5z^2+30z-275=0 | | 8x-1=-2x+1 | | 4+1d=14 | | 153.92/4.32 | | 3+4*5-2=15 | | 59=g+13 | | 64+144=x |